MOTIVASI BERPRESTASI GURU PROFESIONAL DI SMK NEGERI 2 SAWAHLUNTO - Desma Widya Astuti (Universitas Negeri Padang, 2013)
This research background is inherent achievement motivation of professional teachers. The purpose of research to got information how the achievement motivation of professional teachers in SMK Negeri 2 Sawahlunto. This research is population research with a population of 58 professional teachers. Instrument used in this research was the questioners which have been tested for its validity and reliability. In general, the achievement motivation of professional teachers in SMK Negeri 2 Sawahlunto in the category of high length with an average score overall was 4,37. Kata kunci : Motivasi berprestasi; Guru profesional